(untitled) (Research, Society and Development, 2021)
Objective: To investigate the effects of aquatic physical therapy in hospitalized premature infants in the Neonatal Intensive Care Unit. Method: This is a non-randomized clinical trial. The sample consisted of 15 preterm newborns. The personal and clinical data of the preterm newborns were collected from the medical record. They were evaluated on two consecutive days: on the first day, the variables of the study (heart and respiratory rate, peripheral saturation, blood pressure, pain and sleep) were evaluated, soon after the blood puncture for the collection of routine exams, and then, the variables were reassessed. On the second day, the procedures of the first day were repeated, however, after the puncture, aquatic physiotherapy was performed. Results: It was observed that the variables heart rate (p<0,01) and sleep (p<0,01) showed significant differences between pre- and post-intervention. The variables saturation, respiratory rate and pain showed significant differences between pre- and post-procedure of the first day, but not between pre- and post-intervention. However, it was possible to observe a difference between the evaluation after the first day and the second day. Conclusion: The 36 results of the present study indicate an improvement in the physiological parameters, mainly heart rate and sleep, indicating that aquatic physiotherapy may be an important resource to provide comfort and favor the development of the newborn.